A Review on Techno-Economic Perspective of a Smart Grid and its Challenges - Rana, Md Juel; Tareq, Abdulla al; Hasan, Md Mehedi; Aziz, Tareq; Neidhe, Md Mushfiqur Rahman (Control Systems and Optimization Letters, 2024)
This study undertakes a thorough analysis of the techno-economic perspective related to smart grids. It investigates how to improve sustainability and efficiency in power systems by integrating cutting-edge technology. Important elements included in the evaluation include distribution automation, improved metering infrastructure, communication technologies, and the incorporation of renewable energy sources. Examined are the financial effects of implementing smart grids, including cost-benefit analysis, operational effectiveness, and consumer empowerment. The study also lists and analyzes barriers to broad adoption, such as legislative frameworks, cybersecurity threats, and interoperability problems. The study discusses each of these issues in detail, providing insights into the underlying difficulties and possible solutions. It underlines how crucial it is for stakeholders to work together, invest in cutting-edge technology, and change regulations in order to get beyond these challenges and create an energy ecosystem that is more intelligent, effective, and sustainable.